Gerakan Literasi Sekolah pada Tahap Pembiasaan di Sekolah Dasar - Rahmawati, Niken Nur; Sari, Sasmita (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
The research entitled “School Literacy Movement at the Habituation Stage in Elementary Schools” highlights the urgency of fostering early reading habits as a foundation to improve students’ literacy skills in elementary education. This study aims to examine the implementation of the School Literacy Movement (SLM) at the habituation stage in an elementary school (SD X) located in the city. The research design employs a qualitative approach with a descriptive method. The research subjects consist of the principal, classroom teachers, and students, selected through purposive sampling. Data were collected through semi-structured interviews, observation, and documentation. Data analysis used Miles & Huberman’s model, which includes data reduction, data display, and conclusion drawing. Data validity was tested through source and technique triangulation. The findings indicate that the implementation of the SLM at the habituation stage in SD X has been carried out through several main activities, including 15 minutes of reading before lessons begin, the provision of reading corners in each classroom, the use of school bulletin boards, library optimization, community involvement such as parents and local residents, as well as the creation of a text-rich environment around the school. These activities aim to cultivate students’ reading habits, enhance their learning motivation, and develop their skills in comprehending and utilizing various types of reading materials. Keywords: School Literacy Movement, and Habituation Stage